Sexual Creators and Intellectual and Developmental Disabilities: Being Human in Different Ways - Jamieson, Christine (Journal of religion & society. Supplement, 2015)
The essay addresses the challenge of protecting persons with intellectual and developmental disabilities who wish to express their sexuality but may be vulnerable, while also promoting their autonomy and capacity for self-determination. We briefly discuss various restrictions commonly placed on them and the persistent biases that keep us from seeking to truly understand their experiences. Drawing on principlism, the ethic of care, the duty to care, and the wisdom of Jean Vanier, we discuss an ethical framework for assisting persons with intellectual and developmental disabilities and their caregivers in making ethically sound decisions.